2003
DOI: 10.1212/01.wnl.0000052994.54660.58
|View full text |Cite
|
Sign up to set email alerts
|

DHEA treatment of Alzheimer’s disease

Abstract: DHEA did not significantly improve cognitive performance or overall ratings of change in severity in this small-scale pilot study. A transient effect on cognitive performance may have been seen at month 3, but narrowly missed significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 28 publications
0
36
1
Order By: Relevance
“…It is unclear what dose would be required to produce similar effects, if these are possible, in a population with lower baseline DHEA concentrations. Secondly, the use of such high doses of DHEA as used here over the long term, could theoretically lead, via metabolism into active sex steroids, to adverse effects, such as enhanced hormone-sensitive tumour growth (Wolkowitz et al 2003). As a result, future investigations need to proceed with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear what dose would be required to produce similar effects, if these are possible, in a population with lower baseline DHEA concentrations. Secondly, the use of such high doses of DHEA as used here over the long term, could theoretically lead, via metabolism into active sex steroids, to adverse effects, such as enhanced hormone-sensitive tumour growth (Wolkowitz et al 2003). As a result, future investigations need to proceed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extrapolation of such findings in animals to humans is problematic because DHEA concentrations in rodents are significantly lower than in man (Vallee et al 2001). Further, in humans, results have been inconsistent and almost all placebo-controlled trials have found no beneficial effects on memory in healthy old subjects (Barnhart et al 1999;Wolf et al 1997Wolf et al , 1998van Niekerk et al 2001) or patients with Alzheimer's disease (Wolkowitz et al 2003). This could be due to the use of different dosage, variation of period of DHEA administration and age of subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of trials (n = 94) used at least one cognitive outcome, 25,27-29, 51,52,55,57,64,66,68,75,78,[86][87][88][89][90][91][92][93]97,104,106,107,110,112,115,118,119,121,123,125,126,130,131,133,134,[137][138][139][140]143,145,146 with a variety of 16 measures used. ADLs were measured in 55 trials, using 12 measures.…”
Section: Published Trialsmentioning
confidence: 99%
“…Further studies, however, mostly with small series of patients, did not confirm these results (Cuckle et al, 1990;Spath-Schwalbe et al, 1990;Leblhuber et al, 1993). More recently, observational longitudinal studies failed to demonstrate a predictive role of DHEA levels with respect to development of cognitive decline (Barret-Connor and Edelstein, 1994;Berr et al, 1996;Yaffe et al, 1998), and a randomized trial did not show evidence of benefit from treatment with DHEA in patients with Alzheimer's disease (Wolkowitz et al, 2003). Despite this lack of evidence, negative results in previous studies might originate from heterogeneous sample (including different subtypes of dementia) and from inadequacy to focus on selected neuropsychologic fields, as memory and attention, which in experimental models have proven to be favourably affected by DHEA-S administration.…”
Section: Introductionmentioning
confidence: 99%